Pemahaman Masyarakat terhadap Pembatasan Usia Minimal untuk Melangsungkan Perkawinan - Supianto Supianto; Nanang Tri Budiman; Dwi Fefri Kurniasari (Fakultas Hukum Universitas Islam Jember, 2020)
Provisions regarding the minimum age limit in the Marriage Law have been amended with the birth of Amendment to the Marriage Law Number 16 Year 2019. In this law the minimum age of marriage for women is equal to the minimum age of marriage for men, which is 19 (Nineteen) year. The age limit is considered to have matured body and soul to be able to carry out marriage in order to realize the purpose of marriage properly without ending in divorce and get healthy and quality offspring. From the results of the study it was found that the people of the Village of Pontang Ambulu did not know about the change in the minimum limits to carry out the marriage nor did they know about the existence of the Law No. 16 of 2019 which mentions changes in the minimum age limit for marriage.